Pengaruh Perilaku Konsumen terhadap Keputusan Pembelian Kosmetik (Studi Pada Pengguna Kosmetik Revlon di Malang Town Square) - Claudia, Vella Sarah (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2017)
This study aims at analyzing the influence of consumer behavior on purchasing decision towards Revlon cosmetics in Malang Town Square (MATOS) in Malang. This explanatory research explains the relation between research variables through hypothesis testing. This study uses a sample of 100 people selected through purposive sampling technique. The data were collected through questionnaires using a five-point Likert scale as the measurement tool. The test instruments used in this research are validity test, reliability test, classical assumption test, and regression analysis test using SPSS 20.0. The results show that cultural, social, personal, and psychological variables influence purchasing decisions. Social variable is the most dominant variable affecting the purchasing decisions towards Revlon cosmetics.Keywords: cultural, social, personal, psychological, purchase decision